Studi Hadis tentang Berbakti Kepada Orang Tua - Nenden; Erni Isnaeniah; Husnul Qodim (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about filial piety to parents. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about filial piety in the narration of Bukhari no. 5515. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam that filial piety to both parents is jihad. This study concludes that the hadith narrated by Bukhari no. 5515 is relevant to be used as a motivation for jihad in the form of devotion to both parents.